Cost−effective alloy counter electrodes as a new avenue for high−efficiency dye−sensitized solar cells. (10th March 2015) - He, Benlin; Tang, Qunwei; Yu, Liangmin; Yang, Peizhi
Highlights: Pt–Ni alloy CEs are synthesized by an electrochemical codeposition method The dosage of Pt is markedly reduced to fabricate cost−effective CE Alloying of Pt with Ni can favor electronic perturbation for enhanced electrocatalysis The DSSC with PtNi0.75 yields an efficiency of 8.59% Abstract: Pursuit of cost−effective and efficient counter electrodes (CEs) has been a persistent objective for dye−sensitized solar cells (DSSCs). Aiming at reducing fabrication cost without sacrificing power conversion efficiency of DSSCs, here we report the successful design of binary Pt–Ni alloy CEs by a simple cyclic voltammetry technique. Due to the rapid charge transfer ability and electrocatalytic activity, the power conversion efficiency of the DSSC employing binary PtNi0.75 alloy CE has been elevated to 8.59% in comparison with 6.98% from Pt−based solar cell. The impressive results along with simple synthesis highlight the potential application of low−Pt alloys in robust DSSCs.